(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
The reinterpretation of some informations contained in works of the XVIII century allows to recontruct the date and place of discovery of a Roman mosaic panel, depicting the personification of the month of June, preserved at the Hermitage Museum in St. Petersburg, whose provenance was unknown. The emblema was found in 1735 in the suburbs of Rome, at the Torre di Mezzavia of Albano, along the Via Appia Nuova, and entered the collection of Cardinal Pietro Ottoboni. In the area of the discovery there were the remains of a villa of imperial age, which also returned some sculptures.